Nutrient losses in quick cooking rice during processing and storage - Valdez, Anabella G. (2003)
The losses of thiamine (Vitamin B1), riboflavin (Vitamin B2), and total iron in quick cooking rice (QCR from 3 Philippine rice varieties: IR 42, IR 36, nd IR 74 during processing and storage was studied. The nutrients losses and shelf life of the QCR were determined under accelerated condition of 40°C and 100% relative humidity using laminated polyethylene (PE) and co-extruded nylon PE under ordinary and vacuum sealing. Other parameters monitored were proximate composition, microbiological profile and physical and sensory qualities of QCR. he order of micronutrients losses in rice during QCR processing was: Vitamin B1 > total iron > Vitamin B2. While the order of micronutrients loss after QCR processing was crude fat > moisture content > crude fiber > crude ash > crude protein > carbohydrates. The TPC of the test rice varieties used for QCR production in the range of 2.53 - 3.47 log cfu/g were reduced by 41 - 49% after processing. The YMC and Bacillus cereus counts before and after QCR processing remained < 1 log cfu/g. The newly processed QCR had the following physical characteristics: (0.60 - 0.62)Aw; (71.80 - 72.72) L; (-1.58 to -1.40) A; and (3.27 - 3.54) B color; (1.07 - 1.50) volume increase ration; and (2.83 - 3.03) weight increase ratio. The acceptance of ratings of all sensory parameters of QCR from IR 36 and IR 74 evaluated were relatively higher compared to QCR from IR 42. Generally, the QCR from IR 36 was less whiter than the other 2 varieties. The sensitive parameters for stored QCR during accelerated conditions were the micronutrient, Aw and moisture content. Iron losses and moisture content were generally higher in stored QCR in laminated nylon PE vacuum-sealed than in ordinary sealed. Thiamin and riboflavin losses in stored QCR from IR 42 and IR 74 in laminated nylon PE under ordinary sealing were higher than vacuum sealing. Higher losses of iron and thiamin (Vitamin B1) was observed in sorted QCR in co-extruded nylon PE than laminated nylon PE both under ordinary sealing. Vacuum sealing was found to be better in minimizing deterioration of thiamin and riboflavin in stored QCR from IR 42 and IR 74 than ordinary sealing in laminated nylon PE. Laminated nylon PE provided lesser loss of thiamin and iron in stored QCR from IR 36 than in co-extruded nylon PE under ordinary sealing.